The Psychological Condition of STIQ Amuntai Student’s in Learning Arabic - Rifa'i, Ahmad; Hidayati, Erma; Purnamasari, S. (Universitas Muhammadiyah Sumatera Barat, 2021)
This study discussed the psychological condition of STIQ Amuntai students in learning Arabic and the factors that affect the psychological condition of STIQ Amuntai students in learning Arabic. This study aimed to determine the psychological condition of students of the Al-Quran College of Science in learning Arabic, both students with religious education background such as Aliyah/Islamic boarding schools and students with public schools background such as high schools, vocational schools. This study also discussed the factors that influenced the psychological condition of students during learning Arabic. This research is a qualitative descriptive study. The data were collected by observation, interviews, and documentation. The process of data analysis is by examining all observed data from related to Arabic learning, checking the validity of the findings by author participation. The conclusion from this study can be argued that the psychological condition of STIQ Amuntai students in learning Arabic was not good, they were less enthusiastic and confused when learning Arabic. It is due to several factors, namely: diverse school backgrounds and lack insights about Arabic such as a lack of management of Arabic learning materials. Beside that they were faced with various other subject matter and the obligation to memorize al-Quran, thus the interest and enthusiasm gradually diminished. The lecturer background is in accordance with their education and the syllabus is in line with the campus syllabus. The teaching methods were not suitable for students abilities. Campus environment that did not use Arabic both from superiors and students. There were inadequate facilities and infrastructure, such as language laboratories that were not used according to their function.